Results from Over One Year of Follow-Up for Absorbable Mesh Insertion in Partial Mastectomy - Koo, Min Young (Yonsei University College of Medicine, 2011)
PURPOSE: Recently, several clinicians have reported the advantages of simplicity and cosmetic satisfaction of absorbable mesh insertion. However, there is insufficient evidence regardint its long-term outcomes. We have investigated the surgical complications and postoperative examination from the oncologic viewpoint. MATERIALS AND METHODS: From February 2008 to March 2009, 34 breast cancer patients underwent curative surgery with absorbable mesh insertion in Samsung Medical Center. Patient characteristics and follow up results including complications, clinical and radiological findings were retrospectively investigated. RESULTS: The mean age of the study population was 50.1±8.9 years old (range 31-82) with a mean tumor size of 3±1.8 cm (range 0.8-10.5), and the excised breast tissue showed a mean volume of 156.1±99.8 mL (range 27-550). Over the median follow-up period of 18±4.6 months (range 3-25), mesh associated complications, including severe pain or discomfort, edema, and recurrent fluid collection, occurred in nine patients (26.5%). In three cases (8.8%), recurrent mastitis resulted in mesh removal or surgical intervention. In the postoperative radiologic survey, the most common finding was fluid collection, which occurred in five patients (16.1%), including one case with organizing hematoma. Fat necrosis and microcalcifications were found in three patients (9.7%). CONCLUSION: Absorbable mesh insertion has been established as a technically feasible, time-saving procedure after breast excision. However, the follow-up results showed some noticeable side effects and the oncologic safety of the procedure is unconfirmed. Therefore, we suggest that mesh insertion should be considered only in select cases and should be followed-up carefully.